2016
DOI: 10.1371/journal.pone.0167078
|View full text |Cite
|
Sign up to set email alerts
|

The Open Form Inducer Approach for Structure-Based Drug Design

Abstract: Many open form (OF) structures of drug targets were obtained a posteriori by analysis of co-crystals with inhibitors. Therefore, obtaining the OF structure of a drug target a priori will accelerate development of potent inhibitors. In addition to its small active site, Trypanosoma cruzi dihydroorotate dehydrogenase (TcDHODH) is fully functional in its monomeric form, making drug design approaches targeting the active site and protein-protein interactions unrealistic. Therefore, a novel a priori approach was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 55 publications
0
15
0
8
Order By: Relevance
“…It is an enzyme involved in glycerol metabolism as well as gluconeogenesis [32,33]. Finally, DHODH catalyzes the oxidation of dihydroorotate into orotate with concomitant reduction of ubiquinone [34]. DHODH is the rate-limiting step in the pyrimidine de novo biosynthesis pathway and is required to generate UMP, the building block of DNA and RNA necessary to sustain life [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…It is an enzyme involved in glycerol metabolism as well as gluconeogenesis [32,33]. Finally, DHODH catalyzes the oxidation of dihydroorotate into orotate with concomitant reduction of ubiquinone [34]. DHODH is the rate-limiting step in the pyrimidine de novo biosynthesis pathway and is required to generate UMP, the building block of DNA and RNA necessary to sustain life [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant human DHODH was purified, crystallized, and assayed as previously described ( Inaoka et al, 2016 ) without modification. Bovine mitochondrial fractions were prepared as previously described ( Kita et al, 1988 ) and NADH dehydrogenase (complex I), succinate:quinone reductase (complex II), quinol oxidase (complexes III–IV), NADH-cytochrome c reductase (complexes I–III), and succinate-cytochrome c (complexes II–III) activities were assayed following an established method ( Takamiya et al, 1986 ; Miyadera et al, 2001 ; Matsumoto et al, 2008 ; Kido et al, 2010 ; Nihashi et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…All data sets were processed and scaled using HKL-2000 ( Otwinowski and Minor, 1997 ). The structure of the HsDHODH- 9 complex was solved by molecular replacement using the refined protein coordinates of HsDHODH-mii-4-087 complex (PDB code 3W7R) ( Inaoka et al, 2016 ) as a search model. All other structures of HsDHODH inhibitor complexes were solved by molecular replacement using the refined protein coordinates of HsDHODH- 9 complex (PDB code 5ZF4) as a search model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key objective of our study was to discover TbgGK inhibitors that could replace glycerol for combination therapy with AF. Therefore, the effect of the TbgGK inhibitors identified above on the trypanocidal potency of AF was evaluated by the addition of 10 mM each of the secondary hit compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) improved the potency of AF. We found that such compounds shifted the EC 50 of AF to ,0.01 nM ( Table 1).…”
Section: In Vitro Trypanocidal Activity Of Af Plus Tbggk Inhibitormentioning
confidence: 99%